Serving up a healthy education canteen case studies - Leigh, Richard; Heristanidis, Christina; Video Educational Australasia (Australia : Video Educational Australasia, 2006)
This program explores some of the issues facing school canteens today, including health and nutrition, food selection in canteens and influences on food choices. The case study of two schools illustrate how redesigning canteen food is not only possible, but financially viable
Title from title screen
Executive producer, Mark McAuliffe ; camera, Nick Hayward, Amanda Sykes
Voice over: Mark Collard
Keywords: Food preferences; Food portions; Nutrition